2013
DOI: 10.1038/ki.2013.195
|View full text |Cite
|
Sign up to set email alerts
|

Low C4 gene copy numbers are associated with superior graft survival in patients transplanted with a deceased donor kidney

Abstract: Complement C4 is a central component of the classical and the lectin pathways of the complement system. The C4 protein exists as two isotypes C4A and C4B encoded by the C4A and C4B genes, both of which are found with varying copy numbers. Deposition of C4 has been implicated in kidney graft rejection, but a relationship between graft survival and serum C4 concentration as well as C4 genetic variation has not been established. We evaluated this using a prospective study design of 676 kidney transplant patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Our finding that increased copy number of C4A is associated with protection in AMD may have direct implications for therapy, as targeted approaches to molecular constituents of the complement pathway have the potential for early intervention before vision is compromised. This is especially true, in very contrast to most associated single nucleotide variants, as we can directly implicate the relevant gene ( C4A ) and the orientation of the protective effect with increased copy numbers and thus with increased C4A protein levels in serum [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that increased copy number of C4A is associated with protection in AMD may have direct implications for therapy, as targeted approaches to molecular constituents of the complement pathway have the potential for early intervention before vision is compromised. This is especially true, in very contrast to most associated single nucleotide variants, as we can directly implicate the relevant gene ( C4A ) and the orientation of the protective effect with increased copy numbers and thus with increased C4A protein levels in serum [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the deficiency of either C4A or C4B has been associated with the increased susceptibility of infections (18,64,65). Interestingly, it was reported by Bay et al that low C4 gene copy numbers (< 4 total copies of C4 genes) are associated with superior graft survival in patients transplanted with a deceased donor kidney (66). A comprehensive review on the variations of C4 genetic structures and proteins was presented by Blanchong CA et al (36).…”
Section: Diversity Of Complement C4 Genes and Proteinsmentioning
confidence: 99%
“…Some complement proteins are located in the MHC locus (C2, C4), and are also polymorphic [57]. Genetic predisposition to specific polymorphisms may be useful for risk stratifying patients, and indeed polymorphisms in complement C4 [58] but not C3 [59] have been shown to influence renal allograft outcome. In addition, complement concentration is potentiated in response to local inflammation.…”
Section: Factors Which Dictate Complement Activationmentioning
confidence: 99%